2014
DOI: 10.1136/bmjquality.u200548.w2006
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of discharge summary completion by linking to preexisiting patient information databases

Abstract: The discharge summary (DS) is a document that contains the diagnosis, comorbidities, procedures, complications, and future treatment plan for a particular patient after an inpatient hospital stay. The DS is completed by junior medical staff and is delivered to the general practitioner (GP). DS completion is time consuming and tedious, and DSs are usually not completed within the recommended time frame after a patient is discharged. Time spent completing DSs correlate to junior doctor overtime, which costs the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
(6 reference statements)
0
14
1
Order By: Relevance
“…These findings contradict other studies that found that non-index readmission was associated with a longer LOS for that readmission. 12,31 Unlike other studies, [32][33][34] and possibly explaining that shorter LOS in the present study, we found a high rate (>80%) of completion of electronically accessible discharge summaries at the time of next hospital readmission. This could have led to better communication of patients' clinical problems even when their readmission was to a different hospital.…”
Section: Discussioncontrasting
confidence: 92%
“…These findings contradict other studies that found that non-index readmission was associated with a longer LOS for that readmission. 12,31 Unlike other studies, [32][33][34] and possibly explaining that shorter LOS in the present study, we found a high rate (>80%) of completion of electronically accessible discharge summaries at the time of next hospital readmission. This could have led to better communication of patients' clinical problems even when their readmission was to a different hospital.…”
Section: Discussioncontrasting
confidence: 92%
“…Their task was to use existing evidence to create best practice guidelines with particular focus on developing key inclusion elements. A list of 13 elements constituting a "bestpractice" DS was developed, including: (1) patient details, (2) admission diagnosis, (3) discharge diagnosis, (4) investigations (e.g., laboratory tests, imaging tests), (5) procedures (surgical and other interventional procedures), (6) hospital course, (7) allergies, (8) adverse reactions, (9) ceased medications, (10) discharge medications, (11) pending laboratory results, (12) medical problems at discharge, and (13) followup details.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…At our institution, we found that DS completion was a low priority for medical staff as direct patient care generally took precedence. 8 Furthermore, medical staff worked a considerable amount of overtime. Staff were also under considerable pressure to compile the DS within 48 hours of discharge.…”
Section: Problemmentioning
confidence: 99%
“…Staff were also under considerable pressure to compile the DS within 48 hours of discharge. 8 It was felt that these factors adversely affect the quality of the DS.…”
Section: Problemmentioning
confidence: 99%